Effect of Carbon Nanofiber Structure on Crystallization Kinetics of Polypropylene/Carbon Nanofiber Composites - Lee, Sungho; Hahn, Jae Ryang; Ku, Bon-Cheol; Kim, Junkyung (KOREAN CHEMICAL SOC, 2011)
Effect of heat treatment of carbon nanofibers (CNF) on electrical properties and crystallization behavior of polypropylene was reported. Two types of CNFs (untreated and heat treated at 2300 degrees C) were incorporated into polypropylene (PP) using intensive mixing. A significant drop in volume resistivity was observed with composites containing untreated 5 wt % and heat treated 3 wt % CNF. In non-isothermal crystallization studies, both untreated and heat treated CNFs acted as nucleating agents. Composites with heat treated CNFs showed a higher crystallization temperature than composites with untreated CNFs did. TEM results of CNF revealed that an irregular structure of CNFs can be converted into the continuous graphitic structure after heat treatment. Furthermore, STM showed that the higher carbonization temperature leads to the higher graphite degree which presents the larger carbon network size, suggesting that a more graphitic structure of CNFs led to a higher crystallization temperature of PP.
Keywords: REINFORCED THERMOPLASTIC COMPOSITES; NONISOTHERMAL CRYSTALLIZATION; SHIELDING EFFECTIVENESS; POLYMER; FIBERS; TEMPERATURE; BEHAVIOR